A challenging case of spontaneous idiopathic omental infarction in a trisomy 21 patient - Aaron Roy; Jin-Jiun Mah; Theiyallen Ambikapathi; Aung Mra; Firdaus Hayati (Elsevier Ltd, 2022)
Omental infarction (OI) is a rare cause of acute abdominal pain that is often missed out. Due to its non-specific presentation can mimic other commoner conditions such as acute appendicitis, acute diverticulitis, and tuberculosis abdomen. We present a 42-year-old gentleman with trisomy 21 presenting right iliac fossa pain. Examination revealed tenderness in the right lower quadrant and blood parameters showed leucocytosis. With an initial impression of acute appendicitis, the patient was subjected to surgery. Intraoperatively, there were abnormalities to the omentum suggestive of OI, resulting in partial omentectomy. Symptom resolution occurred immediately and the patient was discharged early. OI is a rare cause of acute abdomen that can mimic other abdominal pathologies. In trisomy 21 patients who present with acute abdomen, thorough assessments including preoperative imaging are advisable. Diagnostic laparoscopy is recommended as OI can be managed via minimally invasive surgery, hence ensuring good surgical outcomes.